Can psychological flexibility and prosociality mitigate illness perceptions toward COVID-19 on mental health? A cross-sectional study among Hong Kong adults - Yuen Yu Chong; Wai Tong Chien; Ho Yu Cheng; Angelos P. Kassianos; Andrew T. Gloster; Maria Karekla (BMC, 2021)
Abstract Background The negative impact of COVID-19 pandemic on public mental health can be persistent and substantial over a long period of time, but little is known regarding what psychological factors or processes can buffer such impact. The present study aimed to examine the mediating roles of coping, psychological flexibility and prosociality in the impacts of perceived illness threats toward COVID-19 on mental health. Method Five-hundred and fourteen Hong Kong citizens (18 years or above) completed an online survey to measure illness perceptions toward COVID-19, coping, psychological flexibility, prosociality, and mental health, together with their socio-demographic variables. Structural equation modelling was used to explore the explanatory model that was the best-fit to illustrate the relationships between these constructs. Results Serial mediation structural equation model showed that only psychological flexibility (unstandardised beta coefficient, β = − 0.12, 95% CI [− 0.20, − 0.02], p = 0.031) and prosociality (unstandardised β = 0.04, 95% CI [0.01, 0.08], p = 0.001) fully mediated the relationship between illness perceptions toward COVID-19 and mental health. In addition, psychological flexibility exerted a direct effect on prosociality (standardised β = 0.22, 95% CI [0.12, 0.32], p < 0.001). This best-fit model explained 62% of the variance of mental health. Conclusions Fostering psychological flexibility and prosocial behaviour may play significant roles in mitigating the adverse effects of COVID-19 and its perceived threats on public mental health.